Definition, Conceptualization, and Measurement of Corporate Environmental Performance: A Critical Examination of a Multidimensional Construct - Trumpp, C.; Endrikat, J.; Zopf, C.; Günther, Edeltraud 1965- (2015)
Corporate environmental performance (CEP) has been of fundamental interest in scholarly research during the last few decades. However, there is a great deal of disagreement pertaining to the definition, conceptualization, and adequate measurement of CEP. Our study addresses these issues and provides a methodologically rigorous and comprehensive examination of content validity and construct validity. By integrating the available literature on CEP, we derive a parsimonious definition and theoretically sound framework of the focal construct. Drawing on non-aggregated and publicly available data for a sample of 706 firm-years, we test the construct validity of this framework by means of factor analysis. Our results provide evidence for the multidimensional nature of the focal construct. By contrasting our findings with existing measurement approaches in empirical research, we emphasize several deficiencies with regard to the inferences and conclusions yielded in prior research. Future empirical and practically oriented studies can build on our findings and thus provide more stringent results.
Keywords: Measurement models; ISO 14031; Environmental performance measurement; Environmental management system; Multidimensionality; Construct Validity; Corporate Environmental Performance